Nutritional Status, Food Consumption Pattern and Lifestyle Practices Of Bowen University Students, Iwo - Fakunle, Rachael Ramotu; Adeniyi, Victoria; Ademola, Ayomide Miracle (International Journal on Food, Agriculture and Natural Resources, 2024)
Young adults are vulnerable to obesity, especially as they transition into university life and become responsible for their food consumption and lifestyles. This study assessed the nutritional status, food consumption pattern and lifestyle practices of undergraduates studying at Bowen University, Iwo. A cross-sectional study involving 235 undergraduates was conducted at Bowen university, Iwo. The respondents were assessed with the use of pretested questionnaire to collect data on sociodemographic characteristics, socioeconomic characteristics, body weight, height, body mass index (BMI), food consumption pattern with the use food frequency questionnaire and lifestyle practices. The collected data were analysed with the use of SPSS. The study showed that more than half (63.5%) of the respondents were between the ages of 17-20 years, 57.5% had normal body weight, 5.5% were slightly obese, 12.3% were underweight, and 24.7% were overweight. Cereals, notably, rice was consumed by 33.2% of the respondents on a daily basis and was also the major cereals consumed. This study showed that 22.6% of the respondents engage in physical activities more than three times a week, 23.4% less than three times a week and 63.8% do not engage in any physical activity except school and domestic activities. About 15% of the respondents took alcohol and those who smoked cigarette (4.3%) are far less than those who do not smoke. Most undergraduates have normal body weight, and most of them have low smoking, alcohol drinking and physical activity engagement.